Content Analysis : Evaluation of English Workbook Based on Curriculum 2013 - Fitriazmi, Annesha Desha; Wahyuni , Reni; Aliweh , Ahmed (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: The aim of this research is to find out whether the quality of the English Workbook published by PT. Swadaya Murni used by MTs 13 Jakarta meets the 2013 curriculum criteria Methodology: The researcher used a qualitative method with a content analysis design as a way for researchers to disseminate the quality of English Workbook. The instrument of this research is the BSNP (National Education Standards Board) assessment rubric and to make this research more valid, the researcher conducted several interviews with teachers and several students at MTs 13 Jakarta who used the Workbook. PT. Main Findings: The results of this research only reached 31.25%, which means that the Workbook did not meet the BSNP standard criteria. The results of the interviews also showed that the explanation of the Workbook did not satisfy the teachers and students. However, these worksheets meet students' English language needs because they use language that is appropriate to the context being studied and appropriate to the students' level of knowledge. Novelty/Originality of this study: The novelty of this research reveals that the evaluation of English practice books based on the 2013 Curriculum does not only pay attention to the suitability of the material to the curriculum, but also considers aspects such as depth of understanding of concepts, diversity of question types, creativity in presenting material, and relevance to students' needs in the digital era. At the moment.